Development of In-Situ/Operando Sample Cells for Soft X-ray Transmission Spectromicroscopy at UVSOR-III Synchrotron. Issue 2 (4th March 2017) - Nagasaka, Masanari; Ohigashi, Takuji; Kosugi, Nobuhiro
Abstract : In-situ/operando techniques have been developed for spectromicroscopic studies of heavy elements using hard X-rays with high transmittance in samples and long focal length of optical elements (i.e., long working distance) at photon energies >4 keV. On the other hand, in-situ measurements in the soft X-ray region for spectromicroscopic studies of light elements at deep inner shells and heavy elements at shallow inner shells face significant technical challenges due to several difficulties, including low transmittance and short focal lengths of optical elements. Scanning transmission X-ray microscopy (STXM) in the soft X-ray region is a promising technique for in-situ observation in comparison with other microscopic techniques using electrons and ions, considering its characteristics, such as high resolving power in energy and in space, low radiation damage, and two-dimensional (and three-dimensional) chemical state analysis using near-edge X-ray absorption fine structure.